Impediments to women accountants' career progression in Malaysia / Zubaidah Zainal Abidin, Frances Penafort Ponnu and Marzlin Marzuki - Zainal Abidin, Zubaidah; Frances, Penafort Ponnu; Marzuki, Marzlin (Institute of Research, Development and Commercialization (IRDC), 2006)
This study examines women in the accounting profession, their perceptions of their own career barriers in their organization, and identifies possible reasons why they leave their organizations and ways to retain them. Seven measurable constructs were established: exclusionary environment;family responsibility; workplace benefit; job jlexibility; corporate policies; job stress; and job demand. A multiple regression analysis is used to explain the effects ofwomen accountant s perception of impediments on career progression. Except for elements ofjob stress, where they appear significant in isolation with career progression, most of the findings disclosed no correlations with career advancement ofwomen accountant. Incidentally, marital status is significantly positively related to career progression. The reasons for leaving the organization indicated by the women accountants' are job demand, work family policy, gender discrimination and etc. Work-family policies such as child care and flexi-time are the most consistent benefits quotedby respondents that will enhance retention of employees.